Taxonomy of Neomuscina Townsend (Diptera, Muscidae) from Brazil - Pereira-Colavite, Alessandre; de Carvalho, Claudio J. B. (Zootaxa, 2012)
Neomuscina Townsend includes 41 species distributed throughout the Nearctic and Neotropical Regions. Although the genus has a large number of species, it has been ignored and its taxonomy is confusing and has many flaws. In this work we analyzed the following species recorded for Brazil: Neomuscina atincta Snyder, N. atincticosta Snyder, N. capalta Snyder, N. currani Snyder, N. douradensis Lopes & Khouri, N. goianensis Lopes & Khouri, N. inflexa (Stein), N. instabilis Snyder, N. mediana Snyder, N. mimosa Lopes & Khouri, N. neosimilis Snyder, N. nigricosta Snyder, N. paramediana Lopes & Khouri, N. pictipennis pictipennis (Bigot), N. ponti Lopes & Khouri, N. sanespra Snyder, N. schadei Snyder, N. similata Snyder, N. stabilis (Stein), N. transporta Snyder, N. vitoriae Lopes & Khouri and N. zosteris (Shannon & Del Ponte). Neomuscina nigricosta and N. transporta are new distribution records for Brazil. Three new species are described: Neomuscina anajeensis sp. nov. from Anagé (Bahia), Neomuscina maculata sp. nov. from Botelhos (Minas Gerais) and Neomuscina snyderi sp. nov. from Mata de São João (Bahia). An identification key based on the morphological characters of both male and female is provided. Species distributions are discussed and updated, and the number of species now recorded for Brazil is 29.